Tinjauan Literatur Tentang Peran Rekam Medis Elektronik dalam Peningkatan Mutu Pelayanan Kesehatan - Munawwarah Munawwarah; Sinta Novratilova; Tri Respati Utaminingsih; Sursiyah Sursiyah; Hanik Pratiwi Agustiana; Thessa Nur Auliya; Zakiya Murni Setyawati (Lembaga Pengembangan Kinerja Dosen, 2026)
The quality of healthcare services is highly dependent on the availability of patient data that is timely, accurate, and easily accessible. However, the use of manual medical records still presents several challenges, such as delays in data retrieval, recording errors, and inefficiencies in service processes. Therefore, the implementation of Electronic Medical Records (EMR) is considered a solution to address these issues. Objective: To identify and analyze the role of EMR in improving the quality of healthcare services. Method: This study used a literature review method with data sources obtained from Google Scholar for the period 2022-2026. From 120 identified articles, a selection process based on inclusion criteria resulted in 7 relevant articles for analysis. Results: The findings indicate that EMR improves service efficiency, enhances data accuracy and integration, and supports clinical decision-making. In addition, EMR facilitates better coordination among healthcare providers, streamlines service workflows, and contributes to increased patient satisfaction. However, its implementation still faces challenges, including limited infrastructure, human resource readiness, and data security concerns. Conclusion: EMR plays an important role in improving the quality of healthcare services, particularly in terms of efficiency, data accuracy, and service quality. To optimize its implementation, adequate infrastructure, improved healthcare workforce competence, and strengthened data security systems are required.